Crystal structure of an Effector Histone Methyltransferase Rv2067c from Mycobacterium tuberculosis H37Rv : structural insights into context-dependent substrate recognition structure and dynamics of a GNAT family protein acetyltransferase HP0935 from a gastric pathogen Helicobacter pylori 26695 - Dadireddy, Venkatareddy; Advised by Ramakumar, S (Bangalore : Indian Institute of Science, 2024)
Methylation of histones is one of the important gene regulation mechanisms in eukaryotes. Histone methylation has a role in immune response to the invading pathogens. Pathogens implement effector proteins that evade host defense by modifying the host epigenome i.e., modifications of DNA and histones. Rv2067c, a methyltransferase from Mycobacterium tuberculosis(Mtb), is one such effector secreted by Mtb into the host cell. Rv2067c trimethylates histone H3 at lysine 79 (H3K79). Rv2067c mediated methylation of H3K79 helps Mtb survive in the host cell by controlling apoptosis, necrosis, and host inflammatory and oxidative responses. Interestingly, H3K79 is a substrate of host methyltransferase DOT1L. Though both the enzymes methylate the same residue, H3K79, the substrate context is different. Rv2067c methylates free H3 whereas DOT1L methylates nucleosomal H3. The reverse, however, is not true. In part I of the thesis, to investigate the substrate-context-dependent methylation of H3K79 by Rv2067c and DOT1L, the crystal structure of Rv2067c was determined and compared with that of DOT1L. The structural comparison revealed that both the methyltransferases belong to the same methyltransferase fold: class I or seven-gb(B-strand (7BS). However, the difference lies in the composition and organization of domains. Rv2067c is a homodimer with each monomer containing three domains: catalytic, dimerization, and C-terminal. Whereas DOT1L is a monomer (1537 amino acids) with catalytically active domain spanning the first 416 residues of which residues 4-332 are structured and the rest is disordered with interspersed ga(B-helices. The substrate-context-dependent methylation is mainly determined by the substrate binding sites of Rv2067c and DOT1L. The substrate binding site in Rv2067c is a trough and the active site lies deep inside the protein. Whereas DOT1L interacts with the nucleosome across its length, and the active site is a narrow tunnel. The rotation scan analysis showed that the deeply located active site of Rv2067c becomes inaccessible to the bulky substrate like nucleosome. However, it can be accessible to the extended substrate like free H3 via its trough-like substrate binding region. Molecular dynamics (MD) simulations showed how the occluded active site of Rv2067c widens to accommodate the side chain of H3K79 for methylation. Based on the MD simulations and mode of substrate binding to methyltransferases, a Rv2067c-H3 peptide complex model was proposed where the H3 peptide binds in the substrate-binding trough and places H3K79 in the active site amenable for methylation. The current work provides insights into how the structural differences in the same enzyme class help in determining the context of substrate for the same enzymatic reaction. Acetylation of proteins is an important post-translational modification that has roles in gene regulation, DNA damage repair, central metabolism, signal transduction, and virulence. Protein acetylation is carried out by protein acetyltransferases that add acetyl group to the N-terminal amine or N(Sf(B-amine of lysine side chain of a protein, from an acetyl donor, acetyl-coenzyme A (ACO). Protein acetyltransferases mainly belong to three families viz. GNAT, MYST, and p300/CBP. Eukaryotes contain all three families, whereas prokaryotes have only GNAT members. The number of GNAT members present in prokaryotes varies from species to species. A few systematic studies are available on characterization of acetylomes and the acetyltransferases in prokaryotes. Helicobacter pylori (H. pylori) is a Gram-negative, microaerophilic, spiral-shaped bacterium found in the stomach and is the causative agent of peptic ulcers, chronic gastritis, and gastric cancers. Acetylome analysis of H. pylori revealed that a few dozens of proteins undergo acetylation. H. pylori contains only two GNAT members of which one is a small molecule acetyltransferase, and the other is a putative acetyltransferase, HP0935. The latter was characterized to be a protein acetyltransferase that acetylates a few proteins involved in natural transformation (DprA), DNA mismatch repair (UvrD), and DNA methylation (M.HpyAVIA). As H. pylori contains only one known protein acetyltransferase and multiple acetylated proteins, part II of the thesis aimed to understand the structure of HP0935 and how it acetylates multiple protein substrates. To that, the crystal structure of HP0935 in apo and ACO-bound forms was determined, and the dynamics were studied using Gaussian accelerated molecular dynamics (GaMD) simulations. The structure of HP0935 revealed a typical GNAT fold. The structure contains a long ga(B1-ga(B2 loop and the gb(B6-gb(B7 region. These two regions form a part of the substrate-binding region. A conformational transition was observed in the ga(B1-ga(B2 loop in the presence of ACO, i.e., from distal to proximal. The ACO induced conformational change is supported by the change in the crystal packing and GaMD simulations. In the presence of ACO, the dynamicity in the ga(B1-ga(B2 loop is reduced, and the ga(B1-ga(B2 loop transition is observed for a tiny fraction of trajectory during simulations. In the ACO-HP0935, the gb(B6-gb(B7 region assumed a hairpin which was disordered in apo HP0935 structure. This ordering was attributed to crystal packing based on crystal packing analysis. However, simulations showed that the gb(B6-gb(B7 region could transition between loop and hairpin structures. Clustering of simulation trajectory showed that the dynamicity in the ga(B1-ga(B2 loop and gb(B6-gb(B7 region gave rise to varied shapes and sizes in the substrate-binding region which are likely to allow different protein substrates for acetylation. Our study shows how the co-substrate (ACO) binding affects the dynamics of HP0935. Furthermore, the dynamics in the ga(B1-ga(B2 loop and gb(B6-gb(B7 region are likely to enable HP0935 to accommodate multiple substrates.s
Includes bibliographical references.
PhD;2024;Physics.
Keywords: Mycobacterium tuberculosis; Host-pathogen interaction; Histone methyltransferase; Rv2067c; H3K79 methylation; Helicobacter pylori